The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1109/access.2022.3199353
|View full text |Cite
|
Sign up to set email alerts
|

The Design and Development of a Causal Bayesian Networks Model for the Explanation of Agricultural Supply Chains

Abstract: The balancing of demand and supply in the market is a complex problem because of the dynamic supply chain and environment. It causes uncertain situations and is a limitation in decisions making systems that cannot produce reasonable descriptions to help decision makers eliminate uncertainties. This study proposes the design and development of a Causal Bayesian Networks (CBNs) model for market understanding, which encodes a human-like approach to explain demand and supply events for decision makers. A framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…However, looking at other social aspects (entrepreneurial aspects), the results of empirical research have found positive and prospective phenomena such as innovative work behavior, the need for achievement, and the courage to bear risks, as reflected in the emergence of the fiberglass shipbuilding business groups in Manna District, Bengkulu Selatan Regency. There are 2 important implications resulting from the emergence of an entrepreneurial spirit in this fishing community, including: (1) if this entrepreneurial spirit is empowered consistently, then gradually (due to the trickle-down effect) in the future it will become a form of entrepreneurship that can be developed into a large-scale fiberglass fishing boat industry; and (2) demanding market research (about the interaction between the supply side and the demand side) seriously and consistently (Kliangkhlao et al, 2022;Grymak, 2018).…”
Section: Socio-economic and Entrepreneurial Analysis Of The Developme...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, looking at other social aspects (entrepreneurial aspects), the results of empirical research have found positive and prospective phenomena such as innovative work behavior, the need for achievement, and the courage to bear risks, as reflected in the emergence of the fiberglass shipbuilding business groups in Manna District, Bengkulu Selatan Regency. There are 2 important implications resulting from the emergence of an entrepreneurial spirit in this fishing community, including: (1) if this entrepreneurial spirit is empowered consistently, then gradually (due to the trickle-down effect) in the future it will become a form of entrepreneurship that can be developed into a large-scale fiberglass fishing boat industry; and (2) demanding market research (about the interaction between the supply side and the demand side) seriously and consistently (Kliangkhlao et al, 2022;Grymak, 2018).…”
Section: Socio-economic and Entrepreneurial Analysis Of The Developme...mentioning
confidence: 99%
“…Judging from the economic advantages (cost efficiency), the important urgency of this fiberglass-based ship is seen from its ability to increase its product offerings based on increasing market demand, especially demand from small fishing communities. Another economic advantage (especially in the form of entrepreneurship) is the advantage seen from the impact of fiberglass boat innovation on improving performance through increasing the workability of fishermen (Kliangkhlao et al, 2022;Apriliani et al, 2020;Suardi, 2018).…”
Section: Introductionmentioning
confidence: 99%